Aggregation‐Induced Phosphorescent Emission from ReI Complexes: Synthesis and Property Studies. Issue 9 (1st March 2016) - Chen, Cong; Xu, Yazhou; Wan, Yuchun; Fan, Wei; Si, Zhenjun
Abstract: Four Re I complexes with aggregation‐induced phosphorescent emission (AIPE) were synthesized with the formula Re(CO)3 (Bath‐ n )Br ( n =1 –4 ), where Bath‐1 = 4, 7‐diphenyl‐2‐[4‐(trimethylsilyl)‐phenyl]‐1, 10‐phenanthroline (1 ), Bath‐2 = 4, 7‐diphenyl‐2‐[4‐(dimethylphenylsilyl)phenyl]‐1, 10‐phenanthroline (2 ), Bath‐3 = 4, 7‐diphenyl‐2‐[4‐(methyldiphenylsilyl)phenyl]‐1, 10‐phenanthroline (3 ), and Bath‐4 = 4, 7‐diphenyl‐2‐[4‐(triphenylsilyl)phenyl]‐1, 10‐phenanthroline (4 ), and fully characterized. The single crystals of1 and3 were obtained in the monoclinic crystal system by diffusion of diethyl ether into their dichloromethane solutions. Complexes1 –4 in pure THF ( c ≈ 10 –5 mol L –1 ) mainly present π* → π emission at 370 nm and intraligand charge‐transfer (ILCT) emission at 440 nm, whereas the powder samples of1 –4 solely give lower energy 3 MLCT (metal‐to‐ligand charge transfer) emission at approximately 560 nm. The lifetimes of the powder samples of1 –4 were measured at room temperature to be 0.335 µs, 0.149 µs, 0.289 µs, and 1.301 µs, respectively. Additionally, the emission spectra and the UV/Vis absorption spectra of1 –4 were analyzed in different THF/H2 O mixtures to investigate their AIPE character. Furthermore, the ground states and the UV/Vis absorption spectra of1 –4 were also theoretically simulated at the B3LYP/(LANL2DZ+6‐31G) level. Abstract : Four aggregation‐induced phosphorescent Re I complexes were synthesized and fully characterized, which show mixed π*→π (370 nm)/intraligand charge‐transfer (440 nm) emission in THF solution and pure metal‐to‐ligand charge transfer emission (560 nm) in the solid state. Theoretical simulations of the ground‐state geometry and UV/Vis absorption spectra of these Re I complexes were also investigated.